Conditional Dihydrostreptomycin Resistance in Bacillus subtilis - Staal, S. P. (1972)
Mutants resistant to dihydrostreptomycin were isolated and genetically analyzed in Bacillus subtilis. Two new classes of mutants distinct from the ribosomal strA locus were found. One class, strB, was located between metC3 and ura-1 on the chromosome. The second class, strC, mapped in the spore gene region close to the spoA locus. Both mutant classes were resistant to dihydrostreptomycin during growth but sensitive to the antibiotic during sporulation. Resuspension sporulation experiments with a strB mutant showed that sensitivity to the antibiotic was acquired early in the sporulation process. The germination and outgrowth of strB spores was sensitive to the antibiotic until growth commenced, whereupon the culture was resistant. Thus the mutants are sensitive to dihydrostreptomycin during both sporulation and germination but resistant during the growth phase.